2022
DOI: 10.1177/20412479221109909
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments of Madhuca indica (Mahua) oil-based polymers: A mini review

Abstract: Nowadays, the use of non-edible vegetable oils as the raw material for polymer development is growing in interest because of the scarcity and high demand for crude oil and also because of its eco-friendly approach. The utilization of non-edible oil to synthesize the applicable polymers reduces the usage of petrochemicals. To eliminate the reliance on petrochemicals, it is important to search for and extract alternate and domestic non-edible oils suitable for the synthesis of polymeric materials. This is now a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
(73 reference statements)
1
6
0
Order By: Relevance
“…In Table 2, the physico‐chemical properties of MO, MFA, and PEA are listed, such as their acid value, hydroxyl value, iodine value, saponification value, and specific gravity. As per the determined values of the MO, MFA, and PEA, it can be concluded that the physico‐chemical properties matched the standard values reported in the literature 21,30 . The iodine value of MO decreased in the synthesized PEA, which showed fewer double bonds.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In Table 2, the physico‐chemical properties of MO, MFA, and PEA are listed, such as their acid value, hydroxyl value, iodine value, saponification value, and specific gravity. As per the determined values of the MO, MFA, and PEA, it can be concluded that the physico‐chemical properties matched the standard values reported in the literature 21,30 . The iodine value of MO decreased in the synthesized PEA, which showed fewer double bonds.…”
Section: Resultssupporting
confidence: 81%
“…As per the determined values of the MO, MFA, and PEA, it can be concluded that the physico-chemical properties matched the standard values reported in the literature. 21,30 The iodine value of MO decreased in the synthesized PEA, which showed fewer double bonds. The hydroxyl value of the PEA was 129 mg KOH/g, which was prompt to polymerize with isocyanate.…”
Section: Physico-chemical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to decrease dependency on petrochemicals, it is necessary to find an alternate naturally occurring non-edible oil based materials for the synthesis of polymers. 4 In addition to effectively addressing the issue of pollution and reducing synthetic dependability of polymers on petroleum resources, the use of biodegradable polymers and their composites can also help to reduce the release of greenhouse gases and advance the high-value utilization of biomass resources, which is consistent with the objective of sustainable development and the foundational principle of the circular economy. Finding and extracting natural, non-edible oils that may be used to make polymeric materials becomes essential to reduce the dependency on petrochemicals.…”
Section: Introductionmentioning
confidence: 95%
“…The fibers from the part of plants are classified into bast fibers such as jute, flax, ramie, hemp, kenaf, seed, cotton, coir, kapok, and leaves such as sisal, pineapple, and abaca, grass, and reed fibers such as rice, corn, and wheat, and core fibers examples: hemp, kenaf, and jute, and other kinds of fibers such as wood and roots. 12,13 Plant fibers contain a high amount of cellulose to form framer fiber. All parts of the plants are single-cell fibers, except the seed is the ultimate fiber.…”
Section: Introductionmentioning
confidence: 99%